Sistem Pendukung Keputusan Menggunakan Metode Analytical Hierarchy Process (AHP ) Pada SMK N 1 Muaro Jambi - Kurniawan, Alhadi Qori; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2021)
SMK N 1 Muaro Jambi participated in the selection of achievement teachers made by the Ministry of Education and Culture starting from 2016 which used a decision support system with the Simple Additive Weighting method which was only used for 2 years, then it was no longer used because it was not relevant to the guidelines for selecting outstanding teachers and dedication made by the Ministry of Education and Culture in 2018 until now. Therefore, a decision support system was developed using the Analytical Hierarchy Process (AHP). With Pedagogic, Personality, Social and Professional criteria which follow the Gupres guidelines set by the Ministry of Education and Culture. Because the advantages of the Analytical Hierarchy Process method can translate the criteria into sub-criteria, so that the assessment carried out on each alternative becomes more detailed. And also using the C4.5 algorithm method to improve accuracy in selecting the best teacher.